Aligning Single-Walled Carbon Nanotubes By Means Of Langmuir-Blodgett Film Deposition: Optical, Morphological, and Photo-electrochemical Studies - Giancane, Gabriele; Ruland, Andres; Sgobba, Vito; Manno, Daniela; Serra, Antonio; Farinola, Gianluca M.; Omar, Omar Hassan; Guldi, Dirk Michael; Valli, Ludovico (Advanced Functional Materials, 2010)
An alkoxy-substituted poly(phenylene thiophene) is used in order to suspend single-walled carbon nanotubes in an organic solvent. The suspension is spread on the air–water interface of a Langmuir trough and the floating film is characterized by means of Brewster angle microscopy and UV-visible reflection spectroscopy and the compression isotherm is recorded. The polymer/carbon-nanotube blend is transferred onto different substrates using the Langmuir–Blodgett technique. AFM measurements indicate the formation of globular structures for the samples transferred at low surface-pressure values and a tubular morphology for high-pressure-deposited samples. AFM analysis is repeated on a sample exposed to soft X-rays for about 5h and a highly organized structure of bundles of carbon nanotubes rises up. Samples with different numbers of layers are transferred onto ITO substrates by means of the Langmuir–Blodgett method and are tested as photocathodes in a photo-electrochemical cell. A Voc of 0.18 V, an Isc of 85.8 mA, FF of 40.0%, and η of (6.23×10−3)% are obtained.

Carbon nanostructures for solar energy conversion schemes - Guldi, Dirk Michael; Sgobba, Vito (Chemical Communications, 2011)
Developing environmentally friendly, renewable energy is one of the challenges to society in the 21st century. One of the renewable energy technologies is solar energy conversion - a technology that directly converts daylight into electricity. This highlight surveys recent breakthroughs in the field of implementing carbon nanostructures - fullerenes (0D), carbon nanotubes (1D), carbon nanohorns, and graphene (2D) - into solar energy conversion schemes, that is, bulk heterojunction and dye-sensitized solar cells. © The Royal Society of Chemistry 2011.

Charge carrier dynamics in a ternary bulk heterojunction system consisting of P3HT, fullerene, and a low bandgap polymer - Koppe, Markus; Egelhaaf, Hans-Joachim; Clodic, Ewan; Morana, Mauro; Lueer, Larry; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Ameri, Tayebeh; Brabec, Christoph (Advanced Energy Materials, 2013)
The photoresponse of P3HT:PC BM based organic solar cells can be enhanced by blending the bulk heterojunction with the low band gap polymer Si-PCPDTBT. Organic solar cells containing the resulting ternary blend as the photoactive layer deliver short circuit currents of up to 15.5 mA cm. Morphological studies show modest phase separation without the perturbation of the crystallinity of the P3HT:PC BM matrix, in accordance with the measured acceptable fill factors. Picosecond time-resolved pump-probe spectroscopy reveals that the sensitization of P3HT:PC BM with Si-PCPDTBT involves the transfer of photogenerated positive polarons from the low band gap polymer to P3HT within few hundreds of picoseconds. Intensity dependent experiments in combination with global fitting show that the charge transfer from Si-PCPDTBT to P3HT competes with non-geminate charge carrier recombination of the holes in the Si-PCPDTBT phase with electrons in the PC BM phase, both processes being of diffusive nature. At excitation densities corresponding to steady state conditions under one sun, modelling predicts hole transfer efficiencies exceeding 90%, in accordance with IQE measurements. At higher pump intensities, bimolecular recombination suppresses the hole transfer process effectively. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Electrostatic layer-by-layer construction and characterization of photoelectrochemical solar cells based on water soluble polythiophenes and carbon nanotubes - Sgobba, Vito; Troeger, Anna; Cagnoli, Rita; Mateo-Alonso, Aurelio; Prato, Maurizio; Parenti, Francesca; Mucci, Adele; Schenetti, Luisa; Guldi, Dirk Michael (Journal of Materials Chemistry, 2009)
Positively and negatively charged functionalized polythiophenes and single walled carbon nanotubes were sequentially adsorbed on indium tin oxide electrodes by electrostatic and van der Waals interactions using the layer-by-layer deposition method. The resulting donor/acceptor photoelectrodes were tested as photoelectrochemical cells. Upon illumination, monochromatic incident photoconversion efficiencies of 8.2 and 4.3% were determined for eight stacks of single walled carbon nanotubes with ammonium and sulfonate polythiophene derivatives, respectively. © The Royal Society of Chemistry 2009.

Enhancing photocurrent efficiencies by resonance energy transfer in CdTe quantum dot multilayers: Towards rainbow solar cells - Ruland Palaia, Andres; Schulz-Drost, Christian; Sgobba, Vito; Guldi, Dirk Michael (Advanced Materials, 2011)
The impact of Förster resonant energy transfer (FRET) in CdTe quantum dot (QD) based photoelectrochemical cells is investigated. By deposition of different CdTe QD sizes onto indium on oxide electrodes, FRET across the photoactive film could be obtained, resulting in a 25% enhancement of the photon-to-current efficiency when compared to reference systems that lack FRET. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Facile decoration of functionalized single-wall carbon nanotubes with phthalocyanines via "click chemistry" - Campidelli, Stephane; Ballesteros, Beatriz; Filoramo, Arianna; Diaz Diaz, David; De La Torre, Gema; Torres, Tomas; Rahman, Aminur; Ehli, Christian; Kießling, Daniel; Werner, Fabian; Sgobba, Vito; Guldi, Dirk Michael; et al. (Journal of the American Chemical Society, 2008)
We describe the functionalization of single-wall carbon nanotubes (SWNTs) with 4-(2-trimethylsilyl)ethynylaniline and the subsequent attachment of a zinc-phthalocyanine (ZnPc) derivative using the reliable Huisgen 1,3-dipolar cycloaddition. The motivation of this study was the preparation of a nanotube-based platform which allows the facile fabrication of more complex functional nanometer-scale structures, such as a SWNT-ZnPc hybrid. The nanotube derivatives described here were fully characterized by a combination of analytical techniques such as Raman, absorption and emission spectroscopy, atomic force and scanning electron microscopy (AFM and SEM), and thermogravimetric analysis (TGA). The SWNT-ZnPc nanoconjugate was also investigated with a series of steady-state and time-resolved spectroscopy experiments, and a photoinduced communication between the two photoactive components (i.e., SWNT and ZnPc) was identified. Such beneficial features lead to monochromatic internal photoconversion efficiencies of 17.3% when the SWNT-ZnPc hybrid material was tested as photoactive material in an ITO photoanode. © 2008 American Chemical Society.

Implementation of redox gradients in hydrogen bonded complexes containing N,N-dimethylaniline, flavin and fullerene derivatives - Murakami, Motonobu; Ohkubo, Kei; Hasobe, Taku; Sgobba, Vito; Guldi, Dirk Michael; Wessendorf, Florian; Hirsch, Andreas; Fukuzumi, Shunichi (Journal of Materials Chemistry, 2010)
A variety of supramolecular complexes were formed by associating an electron donor-substituted flavin dyad (10-[4′-(N,N-dimethylamino)phenyl] isoalloxazine: DMA-Fl) and a family of fullerene derivatives that contain single and double hydrogen bond receptors (SRC and DRC). The stoichiometry of the corresponding complexes, that is, DMA-Fl and SRC or DRC, were examined by Job's plot analysis of the absorption changes linked to DMA-Fl at 470 nm. To this end, 1:1 and 1:2 complex stoichiometries were determined for DMA-Fl-SRC and (DMA-Fl) -DRC, respectively. Molecular aggregates in the form of remarkably stable clusters were formed by the fast injection method. Insights into these clusters came from transmission electron microscopy (TEM) measurements, which revealed network configurations for (DMA-Fl-SRC ) with diameters in the range between 200 and 500 nm, while uniform nanoparticles of about 40 nm diameter were discernible for [(DMA-Fl)-DRC]. The highly colored composite clusters were assembled onto an optically transparent electrode covered with nanostructured SnO films by the electrophoretic deposition technique. Important are the photocurrent action spectra providing maximum IPCE values that are twice as high for [(DMA-Fl)-DRC ] than for (DMA-Fl-SRC). To complement these studies the dynamics of electron transfer were investigated by femtosecond laser flash photolysis in the supramolecular clusters (i.e., (DMA-Fl-SRC) and [(DMA-Fl)-DRC ]). As a matter of fact, for the first time we were able to demonstrate the unidirectional electron transfer from the terminal electron donor (N,N-dimethylaniline) moiety to the terminal electron acceptor (fullerene) moiety. © The Royal Society of Chemistry 2010.

Improving photocurrent generation: Supramolecularly and covalently functionalized single-wall carbon nanotubes-polymer/porphyrin donor-acceptor nanohybrids - Rahman, Aminur; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Jux, Norbert; Tchoul, Maxim N.; Ford, Warren T.; Mateo-Alonso, Aurelio; Prato, Maurizio (Chemistry - A European Journal, 2008)
Novel nanohybrids based on covalently and noncovalently functionalized single-wall carbon nanotubes (SWNTs) have been prepared and assembled for the construction of photoactive electrodes. Polymer-grafted SWNTs were synthesized by free-radical polymerization of (vinylbenzyl)trimethylammonium chloride. Poly[(vinylbenzyl)trimethylammonium chloride] (PVBTA) was also noncovalently wrapped around SWNTs to form stable, positively charged SWNT/PVBTA suspensions in water. Versatile donor-acceptor nanohybrids were prepared by using the electrostatic/van der Waals interactions between covalent SWNT-PVBTA and/or noncovalent SWNT/PVBTA and porphyrins (HP and/or ZnP ). Several spectroscopic, microscopic, transient, and photoelectrochemical measurements were taken to characterize the resulting supramolecular complexes. Photoexcitation of the nanohybrids afforded long-lived radical ion pairs with lifetimes as long as 2.2 us. In the final part, photoactive electrodes were constructed by using a layer-by-layer technique on an indium tin oxide covered glass support. Photocurrent measurements gave remarkable internal photon-to-current efficiencies of 3.81 and 9.90% for the covalent ZnP-/SWNT-PVBTA and noncovalent ZnP /SWNT/PVBTA complex, respectively, when a potential of 0.5 V was applied. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.

Innovative inorganic-organic nanohybrid materials: Coupling quantum dots to carbon nanotubes - Schulz-Drost, Christian; Sgobba, Vito; Gerhards, Christina; Leubner, Susanne; Krick Calderon, Rafael; Ruland Palaia, Andres; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2010)
Inorganic meets organic: Covalent bonds (peptide condensation) and noncovalent interactions (π-π stacking) have been employed en route toward versatile donor-acceptor inorganic- organic nanohybrids, QD-pyrene/SWNT. A charge-transfer event within the hybrid transforms the excitonic state of the quantum dot into a charge-transfer state that has a lifetime of several nanoseconds. Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Langmuir-schaefer films for aligned carbon nanotubes functionalized with a conjugate polymer and photoelectrochemical response enhancement - Sgobba, Vito; Giancane, Gabriele; Cannoletta, Donato; Operamolla, Alessandra; Omar, Omar Hassan; Farinola, Gianluca M.; Guldi, Dirk Michael; Valli, Ludovico (ACS Applied Materials and Interfaces, 2014)
Single-walled carbon nanotubes (SWCNTs) were suspended in 1,2-dichloroethane by noncovalent functionalization with a low-band-gap conjugated polymer 1 alternating dialkoxyphenylene-bisthiophene units with benzo[c][2,1,3]thiadiazole monomeric units. The suspended 1/SWCNT blend was transferred onto different solid substrates by the Langmuir-Schaefer deposition method, resulting in films with a high percentage of aligned nanotubes. Photoelectrochemical characterization of 1/SWCNT thin films on indium-tin oxide showed the benefits of SWCNT alignment for photoconversion efficiency. © 2013 American Chemical Society.

Morphology analysis of near IR sensitized polymer/fullerene organic solar cells by implementing low bandgap heteroanalogue C-/Si-PCPDTBT - Ameri, Tayebeh; Khoram, Parisa; Heumüller, Thomas; Baran, Derya; Machui, Florian; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Halik, Marcus; Rathgeber, Silke; Scherf, Ullrich; Brabec, Christoph (Journal of Materials Chemistry A, 2014)
In the current work, we have investigated the morphological aspects of the ternary solar cells based on host matrices of P3HT:PCBM and P3HT:ICBA, using the low bandgap polymer analogues of C- and Si-bridged PCPDTBT as near IR sensitizers, which show noticeably different performance. A direct comparison of these well-functional and poorly functional ternary blend systems provides insights into the bottlenecks of device performance and enables us to set up an initial set of design rules for ternary organic solar cells. Our study reveals the importance of surface energy as a driving force controlling sensitizer location and morphology formation of ternary blends. The interfacial surface energy results indicate that Si-PCPDTBT locates at amorphous interfaces and P3HT crystallites, while C-PCPDTBT tends to accumulate at amorphous interfaces and semi-crystalline (or agglomerated) domains of the fullerene derivatives. GIWAXS and SCLC results support this prediction where adding high content of C-PCPDTBT influences mainly the semi-crystallinity (aggregation) of the fullerene and reduces the electron mobility, but Si-PCPDTBT impacts mainly the P3HT ordering and, in turn, deteriorates the hole mobility. These findings show that the disruption of the fullerene semi-crystalline domains is more detrimental to the device performance than the disruption of the polymer domains.

Multilayer assembly for solar energy conversion - Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael (Fullerenes and Other Carbon-Rich Nanostructures, 2014)
Organizing molecular thin films of electro- and photoactive building blocks provides a versatile platform to the nanoscale control of assembled multilayers and paves the way for the design of functional electronic devices and/or efficient photoenergy conversion devices. Assembly methods, including the Langmuir–Blodgett and the layer-by-layer technique, offer elegant means to realize well-ordered multifunctional thin films on variable surfaces. In this chapter, the fundamental factors and driving forces that govern the adsorption processes of multilayered assemblies are highlighted and numerous intriguing contributions to the field of template-assisted assemblies are presented. Owing to the applicability of these concepts to carbon-based materials – fullerenes and carbon nanotubes – particular attention is paid to the integration of these exceptionally materials combined with light absorbing constituents into nanostructured thin films en route towards versatile electron donor–acceptor nanohybrids for photoconversion schemes.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Carbon nanotubes; Fullerenes; Langmuir Blodgett; Langmuir Schaefer; Layer by layer; Self assembly; Solar cells

P-doped multiwall carbon nanotube/perylene diimide derivative photoelectrochemical cells for photocurrent generation - Troeger, Anna; Ledendecker, Marc; Margraf, Johannes; Sgobba, Vito; Guldi, Dirk Michael; Vieweg, Benito; Spiecker, Erdmann; Suraru, Sabin-Lucian; Wuerthner, Frank (Advanced Energy Materials, 2012)
A perylene diimide (PDI) derivative bearing four chlorine substituents in the bay area is deposited together with pristine multiwall carbon nanotubes (MWNTs) and/or Nafion p-doped MWNTs (p-MWNTs) onto indium tin oxide (ITO) solid substrates by means of air-brushing. The resulting photoanodes are studied in photoelectrochemical cells and reveal highest photocurrent efficiencies when PDI and p-MWNT are combined as photoactive materials, indicating the beneficial effect of Nafion.

Perspectives on electrochemical insertion of lithium in carbon nanotubes - Sgobba, Vito; Guldi, Dirk Michael (Electrochemical Society Interface, 2010)
Carbon nanotubes (CNTs) are emerging materials with high potential in several disciplines, such as electrochemical insertion of Lithium ion batteries is discussed. Lithium ion batteries are the main power source in today's portable electronic devices. The formation of the new SWNT/lithium systems was complementary monitored by in situ galvanostatic charge-discharge, cyclic voltammetry, X-ray diffraction, as well as resistivity measurements. This has shaped the scientific community's view on technological advances in the emerging fields of energy storage devices focusing on Li-ion secondary batteries, supercapacitors, hydrogen storage. It also unveils the impact on contemporary advances and innovations in, for example, electrochemical doping of the Fermi level of CNT for photonic and nanoelectronic applications.

Quantum-dot-sensitized solar cells: Understanding linker molecules through theory and experiment - Margraf, Johannes; Ruland, Andres; Sgobba, Vito; Guldi, Dirk Michael; Clark, Timothy (Langmuir, 2013)
We have investigated the role of linker molecules in quantum-dot-sensitized solar cells (QDSSCs) using density-functional theory (DFT) and experiments. Linkers not only govern the number of attached QDs but also influence charge separation, recombination, and transport. Understanding their behavior is therefore not straightforward. DFT calculations show that mercaptopropionic acid (MPA) and cysteine (Cys) exhibit characteristic binding configurations on TiO2 surfaces. This information is used to optimize the cell assembly process, yielding Cys-based cells that significantly outperform MPA cells, and reach power conversion efficiencies (PCE) as high as 2.7% under AM 1.5 illumination. Importantly, the structural information from theory also helps understand the cause for this improved performance.

Tailoring the Charge Transport Properties of Printable Si-NCs By Conjugated Organic Ligands - Makhdoom, Atif; Sgobba, Vito; Khanzada, Laraib Sarfraz; Fladischer, Stefanie; Spiecker, Erdmann (physica status solidi (a), 2019)
Silicon is dominating the world in photovoltaic technology. The widely used mono crystalline and poly crystalline wafer technologies are expensive to process. As an alternative, technology of silicon nanocrystals (Si-NCs) is a necessity for economical processing of PV modules. In this work, commercially prepared Si-NCs with a mean diameter of 60 nm is utilized with a pretreatment process followed by functionalization. Styryl and 1-ethenyl-4-fluoro benzyl conjugate moieties are grafted on hydrogen-terminated Si-NCs via hydrosilylation of phenylacetylene and 1-ethyny1-4-fluoro benzene, respectively. Thick-films of these functionalized Si-NCs with different thicknesses are prepared and analyzed in a purposed device architecture at room temperature which reveals a p-type character of functionalized Si-NCs films. Detail analysis of current density voltage U V) characteristics of styryl functionalized Si-NCs films shows that the drifting of charge carriers follows a power law relationship V") in the presence of exponentially distributed trap states. Moreover, a unique voltage dependence of the J V curves also reveals a transition between direct and Fowler Nordheim (F N) tunneling mechanisms.
Keywords: 1-ethynyl-4-fluoro benzene; hydrosilylation; phenylacetylene; silicon nanocrystals; space-charge-limited conduction

Theoretical and experimental insights into the surface chemistry of semiconductor quantum dots - Margraf, Johannes; Ruland Palaia, Andres; Sgobba, Vito; Guldi, Dirk Michael; Clark, Timothy (Langmuir, 2013)
We present a series of non-stoichiometric cadmium sulfide quantum-dot (QD) models. Using density functional theory (DFT) and semi-empirical molecular orbital (MO) calculations, we explore the ligand binding and exchange chemistry of these models. Their surface morphology allows for these processes to be rationalized on the atomic scale. This is corroborated by ultraviolet-visible (UV-vis), infrared (IR), and inductively coupled plasma-optical emission spectroscopy (ICP-OES). © 2013 American Chemical Society.

Transient absorption spectroscopy studies on polythiophene-fullerene bulk heterojunction organic blend films sensitized with a low-bandgap polymer - Löslein, Heiko; Ameri, Tayebeh; Matt, Gebhard; Koppe, Markus; Egelhaaf, Hans J.; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Brabec, Christoph (Macromolecular Rapid Communications, 2013)
Recently, the concept of near-infrared sensitization is successfully employed to increase the light harvesting in large-bandgap polymer-based solar cells. To gain deeper insights into the operation mechanism of ternary organic solar cells, a comprehensive understanding of charge transfer-charge transport in ternary blends is a necessity. Herein, P3HT:PCPDTBT:PCBM ternary blend films are investigated by transient absorption spectroscopy. Hole transfer from PCPDTBT-positive polarons to P3HT in the P3HT:PCPDTBT:PCBM 0.9:0.1:1 blend film can be visualized. This process evolves within 140 ps and is discussed with respect to the proposed charge-generation mechanisms. Polythiophene-fullerene bulk heterojunction ternary blend films are investigated by transient absorption spectroscopy. Hole transfer from PCPDTBT-positive polarons to P3HT in the blend film can be visualized. This process evolves within 140 ps and is discussed with respect to the proposed charge-generation mechanisms. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Two similar near-infrared (IR) absorbing benzannulated AZA-bodipy dyes as near-ir sensitizers for ternary solar cells - Min, Jie; Ameri, Tayebeh; Gresser, Roland; Lorenz-Rothe, Melanie; Baran, Derya; Troeger, Anna; Sgobba, Vito; Leo, Karl; Riede, Moritz; Guldi, Dirk Michael; Brabec, Christoph (ACS Applied Materials and Interfaces, 2013)
Ternary composite inverted organic solar cells based on poly(3-hexylthiophen-2,5-diyl) (P3HT) and phenyl-C-butyric acid methyl ester (PCBM) blended with two different near-infrared absorbing benzannulated aza-BODIPY dyes, difluoro-bora-bis-(1-phenyl-indoyl)-azamethine (1) or difluoro-bora-bis-(1-(5-methylthiophen)-indoyl)-azamethine (2), were constructed and characterized. The amount of these two aza-BODIPY dyes, within the P3HT and PCBM matrix, was systematically varied, and the characteristics of the respective devices were recorded. Although the addition of both aza-BODIPY dyes enhanced the absorption of the blends, only the addition of 1 improved the overall power conversion efficiency (PCE) in the near-infrared (IR) region. The present work paves the way for the integration of near-infrared absorbing aza-BODIPY derivatives as sensitizers in ternary composite solar cells. © 2013 American Chemical Society.